Allnex Malaysia Sdn Bhd / Mohamad Iqra Izz Iman Jamaluddin - Jamaluddin, Mohamad Iqra Izz Iman (Faculty of Business and Management, 2023)
I would like to begin by expressing my gratitude and appreciation to God for His abundant blessings that have allowed me to successfully complete my internship. I want to express my sincere gratitude to my advisor, Sir Muhammad Fairuz Bin Jamil, for giving me the opportunity to complete this report with his guidance throughout the entire semester. He provided significant assistance in navigating various perspectives, opinions, advice, and invaluable guidance during the completion of my internship report for MGT666. He assisted me whenever I required help and provided proper guidance to help me complete this report. Additionally, I found his efforts commendable as he provided me with a visual representation of the external world. This will greatly assist me in approaching my internship with a practical and logical mindset. I would like to take this opportunity to express my gratitude to Allnex Malaysia Sdn Bhd for allowing me to participate in their Internship Program fora period of 24 weeks, as required by UiTM's internship duration. I would also like to express my gratitude to my advisor, Mrs. Azliwati Abd Aziz, who holds the position of Indirect Sourcing Specialist for the valuable lessons they have taught me during my internship with them. I am delighted to collaborate and work alongside them. In addition, I would like to express my gratitude to my parents for providing me with constant support, motivation, and invaluable help throughout my journey. Therefore, they are also providing me with the opportunity to continue my studies in this course, which aligns with my desire to pursue my passion and fulfill my dreams in life. If I don't have all of this, it might hinder my ability to successfully complete my studies. Lastly, I would like to express my gratitude to my classmates who have been helping me with gathering information to complete this report. I would like to extend my apologies to the individuals who have assisted me in various capacities but whose names I have not mentioned. I would like to express my gratitude to the esteemed individuals at UiTM Malacca City Campus for their invaluable guidance in helping me complete my report for MGT 666, Internship. It was truly a pleasure to receive their sincere support.